Spectral Test via Discrete Tchebichef Transform for Randomness - Abu, N. A. (Malaysian Society for Cryptology Research, 2011)
Random key plays essential roles in cryptography. NIST statistical test suite for randomness is the most comprehensive set of random tests. It has been popular and used as a benchmark test for randomness. One of the random tests is spectral test. There has been some serious problem in spectral test as pointed out by few researchers. In this paper, an alternative test shall be proposed to replace the spectral test. The distribution of discrete orthonormal Tchebichef transform has been obtained based on computational observation being made on random noise. A recommendation on the new random test setting for short cryptographic keys shall also be made.